Χαρτοφυλάκιον/Scrinium: An integrating activity for monitoring and assessing the learning of classical languages - Sofía Villegas-Rodríguez; Ronald Forero-Álvarez; Fernando Alexander Calderón-Velasco (The Journal of Classics Teaching)
This article presents an adaptation of the recent e-portfolio learning strategy, named Χαρτοφυλάκιον in ancient Greek and Scrinium in Latin, which significantly enhances the learning and assessment of classical languages in a philosophical academic setting. Developed at the University of La Sabana, this approach synergises constructivist and experiential learning theories to actively involve students in their educational journey, encouraging deeper engagement with the acquisition of ancient Greek and Latin. The e-portfolio encompasses a comprehensive spectrum of student work, from translations and grammatical exercises to philosophical reflections and cultural analyses, all while integrating the creative element of ancient artistic inspiration. The assessment of this didactic strategy employs a custom e-rubric, designed to evaluate organisational skills, independent study, engagement with primary sources, artistic integration, and coherent philosophically reflective insights. Feedback garnered from an anonymous student survey indicates that the e-portfolio not only substantiates students’ intellectual growth but also significantly enriches the learning experience, as evidenced by increased student interest and critical inquiry. The results affirm the e-portfolio’s role in fostering a holistic and interactive learning environment that promotes the students’ autonomy and critical thinking. This research contributes to pedagogical discourse by providing a model for applying reflective, project-based learning frameworks to classical studies. This paper is a product of the project Proteus I: Development of Virtual Environments for Experiential Learning in the Humanities.